Hapten-linked conformational equilibria in immunolglobulins XRPC-24 and J-539 observed by chemical relaxation. - Vuk-Pavlović, S (1978)
The interaction of oligogalactan haptens with the murine myeloma proteins XRPC-24 and J-539 has been investigated by the fluorescence temperature-jump method. The relaxation spectrum is composed of two processes, the faster representing hapten assocaition and the slower a protein isomerization. In both cases the concentration dependence of relaxation times and amplitudes was consistent with the general mechanism formulated by Lancet and Pecht (1976, Proc. Natl. Acad. Sci. U.S.A. 73:3549), in which the equilibrium between two conformations of the protein is shifted by hapten binding. The intact proteins and their Fab fragment had identical kinetic behavior, indicating that the conformational changes are located in the Fab region. Temperature dependence analysis for protein J-539 permitted the calculation of activation parameters and led to a consistent energy profile for all the elementary steps. The conformational states are separated by large activation barriers, but have similar free energies. The results suggest that hapten-induced conformational changes in immunoglobulins are more general phenomena than was previously thought.